ETL Tools to Analyze Diagrams’ Performance: Favoring Negotiations in Geodesign Workshops - Christian Rezende Freitas; Ana Clara Mourão Moura (Disegnare con, 2018)
Geodesign is a set of methods to shared construction of alternative futures to a territory. Among the existing methods, Steinitz’s framework proposes analytical and propositional steps. In analytical step the goal is to compose maps identifying vulnerabilities and attractiveness of the area. In propositional step the users design diagrams of projects and policies to the place to be negotiated between the participants. To analyze the diagrams could help support the negotiations. The study presents the construction of methods, using ETL Tools, to describe the characteristics of the diagrams, mainly the locational and topological similarities. The similarities can be used to indentify projects or policies that are equivalent, complementary or conflicting, helping the negotiation process, reducing the time spent in unnecessary discussions. DOI: https://doi.org/10.20365/disegnarecon.20.2018.15